Feasibility of remote interviews in assessing disease severity in patients with major depressive disorder: A pilot study - Sumiyoshi, Tomiki; Morio, Yasunori; Kawashima, Takahiro; Tachimori, Hisateru; Hongo, Seiji; Kishimoto, Taishiro; Watanabe, Koichiro; Otsubo, Tempei; Oi, Hideki; Nakagome, Kazuyuki; Ishigooka, Jun (Neuropsychopharmacology reports, 2024)
Aim Interview quality is an important factor in the success of clinical trials for major depressive disorder (MDD). There is a substantial need to establish a reliable, remote clinical assessment interview system that can replace traditional in‐person interviews. Methods We conducted a multicenter, randomized, unblinded, prospective, cross‐sectional study to assess the reliability of remote interviews in patients with MDD (UMIN000041839). Eligible patients with MDD underwent remote and in‐person sessions of the Montgomery‐Åsberg Depression Rating Scale (MADRS) assessment performed by different raters within 28 days of providing consent. Patients were randomized to a group first assessed using in‐person interviews and secondarily using remote interviews (in‐person‐first group) or a group first assessed by remote interviews and secondarily using in‐person interviews (remote‐first group). Nineteen trained people (15 clinical psychologists, 3 nurses, and 1 clinical laboratory technologist) performed interviews. Results Of 59 patients (in‐person‐first group, n = 32; remote‐first group, n = 27) who completed both remote and in‐person interviews, 51% (n = 30) were women; the mean age was 41.6 years (range, 21–64 years). There was a strong association between remote and in‐person MADRS scores (r = 0.891, kappa = 0.901). An overall intraclass correlation coefficient (ICC) of 0.886 (95% confidence interval, 0.877–0.952) indicated good consistency between MADRS scores in remote and in‐person interviews. The ICC decreased as the severity of depression increased. Conclusion Our results suggest remote interviews are a feasible alternative option to in‐person interviews in assessing symptom severity in MDD patients and could promote clinical trials in Japan. In a multicenter, randomized study of 59 Japanese patients with major depressive disorder, we found that remote interviews are a feasible alternative option to in‐person interviews in assessing symptom severity by the Montgomery‐Åsberg Depression Rating Scale.